Coordinated control of facts devices for improving power system stability - Yu, Tao. (2008)
This thesis proposes a combination of the TCSC and SVC installation to achieve superior performance for enhancing the dynamic stability of a single-machine infinite-bus system and 1 2-area interconnected 4-machine system.